Fabrication of humidity sensor deposited by sol-gel immersion method of nano-cubic structured Znsno3/Zno based thin film - Md Sin, N. D.; Mamat, M. H.; A., Abdul Aziz; Rusop, M. (UiTM Press, 2013)
Nano-cubic Zinc Stannate (ZnSnO3) was synthesis by sol-gel immersion method growth on zinc oxide (ZnO) template prepared by RF magnetron sputtering. Using field emission scanning electron microscopy (FESEM) it was noted that the distribution of nanocubic ZnSnO3 growth on ZnO template (ZnSnO3/ZnO) increase as the precursor solution volume increase. The photoluminescent spectra of ZnSnO3/ZnO reveal emission at 417 nm and 644 nm. The measured humidity sensor has been exhibited in good agreement with the performance by using a nanocubic ZnSnO3/ZnO with a sensitivity ratio of about 209. The response and recovery times nano-cubic ZnSnO3/ZnO were about 409s and 9s respectively. The sensor shows a good repeatability characteristic after had been radiated towards humidity at 4 cycles.